Enhancing students’ performance in learning economics through group investigation model (Research, Society and Development, 2020)
Economics is one of the school subjects that has many relation with real life condition.Economics should be taught by process to make students understand the steps within it. As in High School 1 Bandar. Economics is still taught using lecture method that focused on teacher explanation and not involving students into the lesson. This may affect the students’ performance on learning economics. Hence, this research has objective to enhance students’ performance in learning economics using group investigation learning model. The methodology used both qualitative and quantitative by observing the learning process in three cycles. The subject of the research is students of 10th grade social department in High School 1 Bandar. The result found that, the average score in the early test on economics was 50.50 and increased to 67.22 in cycle I. The score kept on increasing in cycle II for 78.61 and 82.77 in cycle III. While the students’ completeness on economicsshowed the early test had completeness of 43.33%, and enhancefor 55.55% in cycle I, 91.66% in cycle II and 100% in cycle III.Therefore, group investigation learning method can enhance students’ performance.